Double-monatomic metal nano-enzyme material capable of combining chemodynamic therapy and sonodynamic therapy and preparation method of double-monatomic metal nano-enzyme material

Zn/Cu-BSAN-DOX nanoenzyme prepared by surface protection pyrolysis and sequential single-atom synthesis strategies in breast cancer treatment, the combined effect of chemodynamic therapy and acoustic dynamic therapy was achieved, and the doxorubic acid in the prior art was solved The problems of drug resistance and drug efflux have improved the efficiency and immune response of breast cancer treatment.

CN119215197APending Publication Date: 2024-12-31QINGDAO AGRI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411390334.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The prior art has difficulties in building double single-atom nanoenzyme materials that reverse doxorubicin resistance. It is difficult to ensure effective reactive oxygen amplification and prevent doxorubicin drug efflux, resulting in poor breast cancer treatment effect.

Method used

Silica is modified on the surface of ZIF-8 nanoparticles by surface protection pyrolysis strategy to form a core-shell structure, and Cu-TIPP is connected to the mesoporous silica surface through sequential single-atom synthesis strategy, and prepared by combining calcination reduction method. Zinc and copper double single atom nanoparticles form Zn/Cu-BSAN-DOX nanoenzyme, achieving the combined effect of chemodynamic therapy and acoustic dynamic therapy.

Benefits of technology

Through efficient production of reactive oxygen species through multi-path, the resistance to doxorubicin is reversed, the therapeutic effect of breast cancer is improved, and the immune improvement and apoptosis of tumor cells is significantly promoted, and the new preparation strategy of single-atom nanoenzymes and the clinical anti-tumor application paradigm have been expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215197A_ABST
    Figure CN119215197A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biological medicine composite materials, and particularly relates to a double-monatomic metal nano-enzyme material capable of combining chemodynamic therapy and sonodynamic therapy and a preparation method of the double-monatomic metal nano-enzyme material. The preparation method comprises the following steps: modifying silicon dioxide on the surfaces of ZIF-8 nanoparticles by adopting a surface protection pyrolysis strategy to form a core-shell structure; cu-TIPP is connected to the surface of mesoporous silica by adopting a sequential monatomic synthesis strategy, and zinc-copper double monatomic nanoparticles in different spaces are prepared by adopting a calcination reduction method in order to further obtain the zinc-copper double monatomic nanoparticles. Finally, the nano composite material for treating tumors by combining the double-monatomic metal nano enzyme with chemical power and sonodynamic is invented. The invention overcomes the defects of the prior art, ensures that active oxygen is efficiently generated in multiple ways, reverses the drug resistance of adriamycin, prevents the adriamycin drug from being discharged, and improves the treatment effect of breast cancer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical composite materials, and specifically relates to a double single-atom metal nanozyme material that can be used in combination with chemodynamic therapy and sonodynamic therapy for breast cancer and a preparation method thereof. Background Art

[0002] As the most aggressive subtype of breast cancer, triple-negative breast cancer faces the problem of high metastasis rate, resulting in poor prognosis of tumor treatment and high mortality. In order to treat breast cancer, antibiotics such as doxorubicin are widely used. However, due to the serious drug resistance to doxorubicin caused by drug efflux and immunosuppression, the risk of failure of breast cancer treatment is increasing. In recent years, various metal single-atom nanozyme materials have been widely used in the treatment of breast cancer, including zinc single-atom materials, manganese single-atom materials, zinc-copper diatomic materials, etc.

[0003] The double single-atom nanozyme obtained by the sequential single-atom synthesis strategy combined with chemodynamic therapy and sonodynamic therapy for breast cancer treatment is a new and effective method that can solve the shortcomings of low single-atom space utilization and low catalytic efficiency. This technology currently has difficulties in constructing double single-atom nanozyme materials with the ability to reverse doxorubicin resistance, making it difficult to ensure effective reactive oxygen amplification while reversing doxorubicin resistance. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the present invention provides a double single-atom nanozyme and a preparation method thereof that can be combined with chemodynamic therapy and sonodynamic therapy, thereby ensuring efficient multi-pathway production of reactive oxygen species while reversing doxorubicin resistance, preventing doxorubicin drug efflux, and improving the therapeutic effect of breast cancer.

[0005] The present invention provides a double single-atom nanozyme that can be combined with chemodynamic therapy and sonodynamic therapy. The surface protection pyrolysis strategy is used to modify silicon dioxide on the surface of ZIF-8 nanoparticles to form a core-shell structure; the sequential single-atom synthesis strategy is used to connect Cu-TIPP to the surface of mesoporous silica. In order to further obtain zinc-copper double single-atom nanoparticles, the zinc-copper double single-atom nanoparticles in different spaces are prepared by calcination reduction method; the zinc single-atom nanozyme particle size is 65-85nm, the zinc-copper double single-atom nanozyme particle size is 175-185nm, and the double single-atom nanozyme Zn / Cu-BSAN-DOX particle size is 180-190nm; the thickness of the silicon dioxide shell layer is 10-25nm. The above-mentioned particle size range facilitates the hybrid nanozyme to enter tumor cells for treatment.

[0006] The present invention provides a method for preparing a double single-atom nanozyme material that can be combined with chemodynamic therapy and sonodynamic therapy, comprising the following steps:

[0007] (1) Add 9.4-9.5 g Zn(NO3)2 into 400-500 mL methanol solution, and then stir for 0.5 h-1.0 h at 20-40 °C to fully mix to form solution A;

[0008] (2) Add 11-12 g of C4H6N2 to 400-500 mL of methanol solution, and then stir at 20-40°C for 0.5 h-1.0 h to mix thoroughly to form solution B;

[0009] (3) adding the solution A formed in step (1) to the solution B formed in step (2), stirring at 20-40° C. for 1.0 h-2.0 h, collecting the precipitate after centrifugation, washing it 3-5 times with a methanol solution, and drying it at 60-70° C. for 12 h-16 h to obtain ZIF-8 nanoparticles;

[0010] (4) dispersing the ZIF-8 nanoparticles obtained in step (3) in 200-300 mL of methanol solution, adding 5-10 mL of sodium hydroxide solution, and stirring at room temperature for 0.2 h-0.4 h;

[0011] (5) adding 0.1-0.2 g of hexadecyltrimethylammonium bromide (CTAB) and 1-2 mL of tetraethyl orthosilicate (TEOS) to the solution of step (4), stirring at room temperature for 2 h-3 h, washing with ultrapure water for 3-5 times, drying at 60-70 ° C for 12 h-16 h, and collecting ZIF-8@SiO2 nanoparticles;

[0012] (6) 40-50 mL of N,N-dimethylformamide (DMF) and 0.1-0.2 g of triisopropyl phosphate (TIPP) were added to a 250 mL round-bottom flask and mixed, and then 40-50 mL of dimethyl sulfoxide (DMS) solution containing 0.1-0.2 g of copper acetate (Cu(CH3COO)2·H2O) was added to the above solution, refluxed at 170-180°C for 4-5 hours, and about 70-80 mL of DMF was removed, and then 150-200 mL of ice water was added. After mixing evenly, the remaining solution was cooled to room temperature, allowed to stand for 1-2 hours, and then centrifuged, washed with water, and vacuum dried at 120-130°C for 3-4 hours to obtain Cu-TIPP particles;

[0013] (7) Disperse 15-20 mg of the Cu-TIPP particles obtained in step (6) and 400-500 mg of the ZIF-8@SiO2 particles obtained in step (5) in 100-120 mL of DMF, stir at 175-180° C. for 1-2 h, add 280-300 mg of TIPP, continue stirring at 110-120° C. for 1-2 h to obtain a clear solution, cool to room temperature, add 20-30 mL of 170-180 mg of α, α'-dibromo-p-xylene, DMF, and vigorously stirred for 20-30 minutes, after mixing evenly, stirred at 110-120°C for 40-50 hours, the mixed suspension was centrifuged, and washed three times with DMF and ethanol respectively, and then vacuum dried at 80-90°C for 10-12 hours to obtain a solid powder, and then the solid powder was placed in a tube furnace and calcined at 800-900°C and a heating rate of 5-8°C / min in a H2 / Ar (5% H2) atmosphere for 1-2 hours, and the calcined material was etched with 0.01-0.02MNH4HF2 solution at 60-70°C for 10-20 minutes, centrifuged and washed three times with water, and finally freeze-dried to obtain Zn / Cu-BSAN material;

[0014] (8) 0.1-0.2 g Zn / Cu-BSAN material was suspended in 100-110 mL ethanol, and then 20-30 mL 0.2-0.3 M ethylene disulfide solution was added, stirred at room temperature for 20-25 hours, centrifuged and washed with ethanol three times, and dried under vacuum at room temperature to obtain Zn / Cu-BSAN-SH particles;

[0015] (9) 10-12 mg of DOX·HCl and 25-30 mg of acetylthioacetate SATA were placed in a 10 mL test tube and dissolved with 3-5 mL of DMF, and then 5-10 μL of triethylamine was added to the test tube and stirred for 2-3 h to obtain a SATA-substituted doxorubicin DOX-SATA solution, which was then diluted with 5-10 mL of water, extracted twice with 5-10 mL of ethyl acetate, and then washed three times with 1% hydrochloric acid, saturated sodium carbonate and saturated brine in sequence, and then concentrated by rotary evaporation to obtain DOX-SATA particles;

[0016] (10) 4 mg of the purified DOX-SATA particles obtained in step (9) were dissolved in 2-5 mL of DMF, and the DMF was mixed with 3-4 mg of hydroxylamine hydrochloride (0.5 M) and 2-5 μL of triethylamine. After the chemical reaction was continued in the mixed solution for 1 hour, the product was purified and dried to obtain DOX-SH particles;

[0017] (11) Dissolve 10-15 mg of DOX-SH particles obtained in step (10) in 10-15 mL of DMSO solution, then add 2-5 mg of Zn / Cu-BSAN-SH obtained in step (8), stir at room temperature for 24 hours and centrifuge at 14000 rpm for 10 min, and finally freeze-dry to obtain Zn / Cu-BSAN-DOX nanoparticles.

[0018] Preferably, the concentration of Zn(NO3)2 in the methanol solution in step (1) is 18-20 mg·mL -1 The concentration of C4H6N2 in step (2) is 20-25 mg·mL -1 .

[0019] Preferably, the ZIF-8 nanoparticles described in step (3) are synthesized by reacting 90-97% by weight of methanol, 4-6% by weight of distilled water, 0.01%-0.09% by weight of Zn(NO3)2, and 0.1%-0.3% by weight of C4H6N2.

[0020] Preferably, the concentration of sodium hydroxide in step (4) is 60-80 mg·mL -1 The mass of cetyltrimethylammonium bromide (CTAB) in step (5) is 1-2 mg·mL -1 The concentration of tetraethyl orthosilicate (TEOS) is 15-20 mg·mL -1 .

[0021] Preferably, the ZIF-8@SiO2 nanoparticles in step (5) contain 70-85% by weight of ZIF-8 and 15-30% by weight of silicon dioxide.

[0022] Preferably, the TIPP concentration in the DMF solution in step (6) is 2-5 mg·mL -1 , the concentration of Cu(CH3COO)2·H2O in dimethyl sulfoxide is 2-5 mg·mL -1 .

[0023] Preferably, the mass ratio of Cu-TIPP to ZIF-8@SiO2 in step (7) is 1:20-1:25, and the concentration of Cu-TIPP in the DMF solution is 2-3 mg·mL -1 The concentration of ZIF-8@mSiO2 in DMF solution is 4-5 mg·mL -1 , the concentration of α,α'-dibromo-p-xylene in DMF solution is 6-9 mg·mL -1 .

[0024] Preferably, the concentration of Zn / Cu-BSAN in the ethanol solution in step (8) is 1-2 mg·mL -1 The volume ratio of ethanol solution to dithioethylene glycol solution is 3:1-5:1, and the concentration of DOX·HCl in DMF solution is 3-4 mg·mL -1 , the concentration of acetylthioacetate (SATA) in DMF solution is 6-9 mg·mL -1 The concentration of hydroxylamine hydrochloride in DMF solution is 1-2 mg·mL -1 , the volume ratio of triethylamine and DMF is 1:1000-1:2000.

[0025] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0026] (1) The present invention constructs a hybrid nanozyme with chemodynamic therapy and sonodynamic therapy, which ensures effective reactive oxygen amplification while reversing doxorubicin resistance and improves the efficiency of tumor treatment.

[0027] (2) The present invention effectively integrates chemodynamic therapy and sonodynamic therapy, produces a large amount of reactive oxygen species through dual pathways, and effectively reverses the doxorubicin resistance problem in current breast cancer treatment.

[0028] (3) The preparation method of the present invention has mild reaction conditions, and the prepared materials have good biosafety and biocompatibility, and have good clinical transformation potential.

[0029] (4) The present invention designs dual single-atom nanozymes Zn / Cu-BSAN-DOX-NPs, which damage the mitochondria of mesenchymal stem cells (MSCs) and 4T1 cells through reactive oxygen species (ROS) amplification, thereby reversing BC-DOX resistance; improve the in situ self-supply of H2O2 by activating nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) to release DOX; the amplification of reactive oxygen species is triggered by enhanced chemodynamic therapy (CDT) and sonodynamic therapy (SDT) of Zn / Cu-BSAN N, which effectively reverse DOX resistance by breaking the hyaluronic acid (HA) barrier and DOX efflux; the present invention significantly promotes immune improvement through ROS amplification, including DC maturation, T cell activation and polarization of M1 macrophages. As a "hexagonal" anti-tumor fighter, Zn / Cu-BSAN-DOX NPs show great potential in the treatment of multimodal DOX-resistant breast cancer, which further expands the new preparation strategy and clinical anti-tumor application paradigm of single-atom nanozymes. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1These are transmission electron micrographs of the hybrid nanozymes in Example 1, including (a) ZIF-8 nanoparticles; (b) ZIF-8 encapsulated silica nanoparticles; (c) Zn / Cu-BSAN nanoparticles; and (d) high-magnification transmission images of Zn / Cu-BSAN-DOX nanoparticles.

[0031] Figure 2 These are characterization diagrams of the zinc-copper double single atom in Example 1, including (a) XANES spectrum of zinc single atom, (b) Fourier transform of R edge, (c) Fourier transform of K edge, (dg) wavelet transform of zinc element, zinc oxide, zinc phthalocyanine, and zinc single atom; (h) XANES spectrum of copper single atom, (i) Fourier transform of R edge, (j) Fourier transform of K edge, (kn) wavelet transform of copper element, copper oxide, copper peroxide, and zinc single atom.

[0032] Figure 3 Figure 1 shows the in vitro performance of ROS amplification of Zn / Cu-BSAN-DOX NPs in Example 1, including (a) transmission electron microscopy images of Zn / Cu-BSAN-DOX NPs at different time points in the presence of pH 7.2 and pH 6.5+H2O2(150mM)+GSH(10mM), (b) release curve of DOX, (c) ESR spectrum (·OH) of Zn / Cu-BSANs+H2O2(150mM), (d) degradation of SOSG by Zn / Cu-BSANs+US at different treatment times, (e) Zn / Cu-BSANs+US(1.0W·cm -2 , 1.0MHz, 5min) ESR spectrum (1O 2 ), (f) ROS release curve of Zn / Cu-BSAN-DOX, (g) catalytic performance of different nanoparticles (pH: 4.5, H2O2: 150 mM, US: 1.0 W·cm -2 , 1.0MHz, 5 minutes), where (G1)Control, (G2)US, (G3)DOX, (G4)Zn SACs NPs, (G5)Zn / Cu-BSAN NPs, (G6)Zn / Cu-BSAN-DOX NPs, (G7)Zn / Cu-BSAN-DOXNPs+US.US: 1.0W·cm -2 ,1.0MHz,5min.

[0033] Figure 4This is the evaluation of the reversal of DOX resistance by Zn / Cu-BSAN-DOX NPs in Example 1, wherein (ab) are the expression of HAS2 (a) and HA (b) of mesenchymal stem cells in the supernatant of 4T1 cells after different treatments, (c) quantification of ATP concentration of 4T1 cells after different treatments, and (d) protein blotting of P-gp in 4T1 cells after different treatments, wherein (G1) Control, (G2) US, (G3) DOX, (G4) Zn SACs NPs, (G5) Zn / Cu-BSAN NPs, (G6) Zn / Cu-BSAN-DOX NPs, (G7) Zn / Cu-BSAN-DOX NPs+US. US: 1.0 W·cm-2, 1.0 MHz, 5 min.

[0034] Figure 5 In vivo antitumor evaluation of Zn / Cu-BSAN-DOX nanoparticles in Example 1, including (a) tumor tissue photos, (b) average tumor volume line graph, (c) average tumor weight line graph, where (G1) Control, (G2) US, (G3) DOX, (G4) Zn SACs NPs, (G5) Zn / Cu-BSAN NPs, (G6) Zn / Cu-BSAN-DOX NPs, (G7) Zn / Cu-BSAN-DOX NPs+US. US: 1.0 W·cm -2 ,1.0MHz,5min.

[0035] Figure 6 HE (a) and TUNNEL staining (b) of wound sections of different groups at day 10 of treatment in Example 1. Scale bar: 100 μm, where (G1) Control, (G2) US, (G3) DOX, (G4) Zn SACs NPs, (G5) Zn / Cu-BSANNPs, (G6) Zn / Cu-BSAN-DOX NPs, (G7) Zn / Cu-BSAN-DOX NPs+US. US: 1.0 W·cm -2 ,1.0MHz,5min. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0037] The present invention provides a hybrid nanozyme material that can be combined with chemodynamic therapy and sonodynamic therapy and a preparation method thereof, which ensures efficient multi-pathway generation of reactive oxygen species while reversing doxorubicin resistance, preventing doxorubicin drug efflux, and improving the therapeutic effect of breast cancer.

[0038] Example 1

[0039] The present invention provides a method for preparing a hybrid nanozyme material that can be combined with chemodynamic therapy and photothermal therapy, comprising the following steps:

[0040] (1) 9.4168 g of Zn(NO3)2 was added to 500 mL of methanol solution, and then stirred at 20°C for 1.0 h to fully mix to form solution A;

[0041] (2) 11.0843 g of C4H6N2 was added to 400 mL of methanol solution, and then stirred at 20 °C for 0.5 h to fully mix to form solution B;

[0042] (3) adding the solution A formed in step (1) to the solution B formed in step (2), stirring at 20° C. for 1.0 h, collecting the precipitate after centrifugation, washing it three times with a methanol solution, and drying it at 60° C. for 12 h to obtain ZIF-8 nanoparticles;

[0043] (4) dispersing the ZIF-8 nanoparticles obtained in step (3) in 200 mL of methanol solution, adding 5 mL of sodium hydroxide solution, and stirring at room temperature for 0.2 h;

[0044] (5) adding 0.15 g of hexadecyltrimethylammonium bromide (CTAB) and 1.2 mL of tetraethyl orthosilicate (TEOS) to the solution of step (4), stirring at room temperature for 2 h, washing with ultrapure water for 3 times, and drying at 60 ° C for 12 h to collect ZIF-8@SiO2 nanoparticles;

[0045] (6) 50 mL of N,N-dimethylformamide (DMF) and 0.175 g of triisopropyl phosphate (TIPP) were added to a 250 mL round-bottom flask and mixed. Then, 50 mL of dimethyl sulfoxide (DMS) solution containing 0.1198 g of copper acetate (Cu(CH3COO)2·H2O) was added to the above solution, refluxed at 175°C for 4 hours, and about 80 mL of DMF was removed. Then, 200 mL of ice water was added and mixed well. The remaining solution was cooled to room temperature, allowed to stand for 1 hour, and then centrifuged, washed with water, and vacuum dried at 120°C for 4 hours to obtain Cu-TIPP particles.

[0046] (7) 15 mg of the Cu-TIPP particles obtained in step (6) and 500 mg of the ZIF-8@SiO2 particles obtained in step (5) were dispersed in 100 mL of DMF. After stirring at 175°C for 1 h, 285 mg of TIPP was added and stirring was continued at 110°C for 1 h to obtain a clear solution. After cooling to room temperature, the solution was added to 20 mL of DMF containing 175 mg of α, α'-dibromo-p-xylene and stirred vigorously for 20 min. After mixing evenly, the solution was stirred at 110°C for 48 h. The mixed suspension was centrifuged and washed three times with DMF and ethanol respectively. After vacuum drying at 80°C for 12 h, a solid powder was obtained. The solid powder was then placed in a tube furnace and calcined at 800°C and a heating rate of 5°C / min in a H2 / Ar (5% H2) atmosphere for 1-2 h. The calcined material was heated to 0.02 M The NH4HF2 solution was etched at 60 °C for 15 min, centrifuged and washed with water three times, and finally freeze-dried to obtain the Zn / Cu-BSAN material;

[0047] (8) 0.1 g Zn / Cu-BSAN material was suspended in 100 ethanol, and then 20 mL 0.24 M ethylene disulfide solution was added, stirred at room temperature for 24 h, centrifuged and washed with ethanol three times, and dried under vacuum at room temperature to obtain Zn / Cu-BSAN-SH particles;

[0048] (9) 10.5 mg of DOX·HCl and 25.2 mg of acetylthioacetate SATA were placed in a 10 mL test tube and dissolved with 3 mL of DMF, and then 6 μL of triethylamine was added to the test tube and stirred for 3 h to obtain a SATA-substituted doxorubicin DOX-SATA solution, which was then diluted with 5 mL of water and extracted twice with 8 mL of ethyl acetate, and then washed three times with 1% hydrochloric acid, saturated sodium carbonate and saturated brine in sequence, and then concentrated by rotary evaporation to obtain DOX-SATA particles;

[0049] (10) 4 mg of the purified DOX-SATA particles obtained in step (9) were dissolved in 2 mL of DMF, and DMF was mixed with 3 mg of hydroxylamine hydrochloride (0.5 M) and 2 μL of triethylamine. After the chemical reaction was continued in the mixed solution for 1 hour, the product was purified and dried to obtain DOX-SH particles;

[0050] (11) Dissolve 10 mg of DOX-SH particles obtained in step (10) in 10 mL of DMSO solution, then add 2 mg of Zn / Cu-BSAN-SH obtained in step (8), stir at room temperature for 24 h and centrifuge at 14000 rpm for 10 min, and finally freeze-dry to obtain Zn / Cu-BSAN-DOX nanoparticles.

[0051] Figure 1The transmission electron microscopy of ZIF-8 prepared in Example 1 shows that the diameter of ZIF-8NP with uniform regular dodecahedral structure is ( Figure 1 a) Increased from 80nm to 100nm after coating with SiO2 ( Figure 1 b). After loading DOX on Zn / Cu-BSAN with a diameter of 180 nm, the diameter of Zn / Cu-BSAN-DOX NPs increased to about 180 nm ( Figure 1 c, 1d).

[0052] Figure 2 The characterization diagram of the zinc-copper double single atom in Example 1 shows a near-edge structure that is significantly different from that of zinc and zinc oxide, but similar to that of zinc phthalocyanine, indicating that the local coordination environment of Zn is similar to that of porphyrin zinc ( Figure 2 a), the X-ray absorption fine structure spectra of zinc atoms at the K edge and R edge show that the Zn element in the hybrid nanozyme exists in a Zn-N coordination structure ( Figure 2 b and 2c), the wavelet transform image further confirmed that the structure of the zinc single atom in the hybrid nanozyme is consistent with that in zinc phthalocyanine, both of which are Zn-N four-coordinate structures ( Figure 2 d-2g). K-edge XANES spectrum of Cu ( Figure 2 h) shows that there are some +2 positive charges in Zn / Cu-BSAN. EXAFS in r space ( Figure 2 i) and k-space ( Figure 2 j) shows that the Cu element in the hybrid nanozyme exists in a Cu-N coordination structure. In addition, compared with copper foil, Cu2O and CuO, Zn / Cu-BSAN has only one WT maximum in k space (4A -1 ), which is consistent with Cu-N bonding ( Figure 2 k-2n). This further confirms that the Cu atoms in Zn / Cu-BSAN exist in the form of single atoms coordinated with N atoms.

[0053] Figure 3 The in vitro performance diagram of ROS amplification of Zn / Cu-BSAN-DOX NPs in Example 1 shows that Zn / Cu-BSAN-DOX NPs maintain structural stability and integrity in simulated blood at pH 7.2, while exhibiting rapid structural destruction under simulated conditions of the tumor microenvironment (pH 6.5+H2O2+GSH). Figure 3 a). Nanoparticles rapidly initiate a response to GSH, leading to the release of DOX upon reaching the tumor site ( Figure 3 b). Electron spin resonance (ESR) analysis confirmed the generation of ·OH from Zn / Cu-BSAN ( Figure 3c), indicating that Zn / Cu-BSAN has peroxidase activity. The fluorescence spectrum of singlet oxygen sensor green (SOSG) shows that Zn / Cu-BSAN-DOX NPs can continuously promote the occurrence of sonochemical reactions under US irradiation and produce more 1 O2( Figure 3 d), ESR confirms this ( Figure 3 e). Fluorescence spectrum of ROS ( Figure 3 f) The responsiveness of Zn / Cu-BSAN-DOX NPs to H2O2 and US signals was further demonstrated, and the combined stimulation of H2O2 and US enhanced the amplification of ROS. The TMB oxidation performance of Zn-SAC and Zn / Cu-BSAN at different concentrations was analyzed and compared to evaluate the advantages of BSAN's catalytic activity over single-atom nanozymes ( Figure 3 g). At the same concentration and simulated TME, Zn / Cu-BSAN exhibited stronger TMB oxidation than Zn-SAC, indicating that BSAN has stronger peroxide catalysis ability. In addition, the addition of US can further enhance the TMB oxidation ability of Zn / Cu-BSAN, indicating that Zn / Cu-BS AN has excellent sonodynamic properties and promotes the amplification of ROS.

[0054] Figure 4 The evaluation of the reversal of DOX resistance by Zn / Cu-BSAN-DOX NPs in Example 1 is as follows: Figure 4 As shown in a, the results of Elisa analysis of mesenchymal stem cell supernatant showed that ROS-induced mesenchymal stem cell damage led to the downregulation of HAS2. At the same time, Zn / Cu-BSAN-DOX NPs treatment also significantly reduced the HA content in the extracellular matrix of 4T1 cells ( Figure 4 b), which confirmed the disruption of the barrier protection provided by Zn / Cu-BSAN-DOX NPs to MSCs. In addition, ROS amplification led to severe mitochondrial damage in 4T1 cells, subsequently blocking ATP supply ( Figure 4 c), seriously affecting the transmembrane transport of P-gp, subsequently leading to downregulation of P-gp expression ( Figure 4 d).

[0055] Figure 5 In vivo antitumor evaluation of Zn / Cu-BSAN-DOX nanoparticles in Example 1, there was no significant reduction in tumor volume in mice treated with DOX for 7 days, while tumor reduction was observed during treatment with Zn SAC, Zn / Cu-BSAN, and Zn / Cu-BSAN-DOX NPs compared with the control and DOX-treated groups ( Figure 5 a). The above results are consistent with Figure 5The results in b-5c are consistent, indicating that Zn / Cu-BSAN-DO X NPs have significant anti-DOX resistance and good biocompatibility.

[0056] Figure 6 The terminal deoxynucleotidyl transferase dUTP-Nick end labeling (TUNEL) assay was performed on the wound sections of different treatment groups on the 10th day in Example 1 ( Figure 6 a) and hematoxylin and eosin (H&E) staining ( Figure 6 b) showed that Zn / Cu-BSAN-DOX+US treatment induced significantly higher apoptosis in 4T1 tumor cells compared with other treatment groups.

[0057] The above-mentioned embodiments only express the implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A dual single-atom nanozyme that can be combined with chemodynamic therapy and sonodynamic therapy, characterized in that: A surface protection pyrolysis strategy was adopted to modify silica on the surface of ZIF-8 nanoparticles to form a core-shell structure; a sequential single-atom synthesis strategy was adopted to connect Cu-TIPP to the surface of mesoporous silica, and in order to further obtain zinc-copper double single-atom nanoparticles, a calcination reduction method was adopted to prepare zinc-copper double single-atom nanoparticles in different spaces; the particle size of the zinc single-atom nanozyme particles was 65-85nm, the particle size of the zinc-copper double single-atom nanozyme particles was 175-185nm, and the particle size of the double single-atom nanozyme Zn / Cu-BSAN-DOX particles was 180-190nm; the thickness of the silica shell layer was 10-25nm.

2. A method for preparing a double single-atom nanozyme material that can be combined with chemodynamic therapy and sonodynamic therapy, characterized in that: The following steps are involved: (1) Add 9.4-9.5 g Zn(NO3)2 into 400-500 mL methanol solution, and then stir for 0.5 h-1.0 h at 20-40 °C to fully mix to form solution A; (2) Add 11-12 g of C4H6N2 to 400-500 mL of methanol solution, and then stir at 20-40°C for 0.5 h-1.0 h to mix thoroughly to form solution B; (3) adding the solution A formed in step (1) to the solution B formed in step (2), stirring at 20-40° C. for 1.0 h-2.0 h, collecting the precipitate after centrifugation, washing it 3-5 times with a methanol solution, and drying it at 60-70° C. for 12 h-16 h to obtain ZIF-8 nanoparticles; (4) dispersing the ZIF-8 nanoparticles obtained in step (3) in 200-300 mL of methanol solution, adding 5-10 mL of sodium hydroxide solution, and stirring at room temperature for 0.2 h-0.4 h; (5) adding 0.1-0.2 g of hexadecyltrimethylammonium bromide (CTAB) and 1-2 mL of tetraethyl orthosilicate (TEOS) to the solution of step (4), stirring at room temperature for 2 h-3 h, washing with ultrapure water for 3-5 times, drying at 60-70 ° C for 12 h-16 h, and collecting ZIF-8@SiO2 nanoparticles; (6) 40-50 mL of N,N-dimethylformamide (DMF) and 0.1-0.2 g of triisopropyl phosphate (TIPP) were added to a 250 mL round-bottom flask and mixed, and then 40-50 mL of dimethyl sulfoxide (DMS) solution containing 0.1-0.2 g of copper acetate (Cu(CH3COO)2·H2O) was added to the above solution, refluxed at 170-180°C for 4-5 hours, and about 70-80 mL of DMF was removed, and then 150-200 mL of ice water was added. After mixing evenly, the remaining solution was cooled to room temperature, allowed to stand for 1-2 hours, and then centrifuged, washed with water, and vacuum dried at 120-130°C for 3-4 hours to obtain Cu-TIPP particles; (7) Disperse 15-20 mg of the Cu-TIPP particles obtained in step (6) and 400-500 mg of the ZIF-8@SiO2 particles obtained in step (5) in 100-120 mL of DMF, stir at 175-180° C. for 1-2 h, add 280-300 mg of TIPP, continue stirring at 110-120° C. for 1-2 h to obtain a clear solution, cool to room temperature, add 20-30 mL of 170-180 mg of α, α'-dibromo-p-xylene, DMF, and vigorously stirred for 20-30 minutes, after mixing evenly, stirred at 110-120°C for 40-50 hours, the mixed suspension was centrifuged, and washed three times with DMF and ethanol respectively, and then vacuum dried at 80-90°C for 10-12 hours to obtain a solid powder, and then the solid powder was placed in a tube furnace and calcined at 800-900°C and a heating rate of 5-8°C / min in a H2 / Ar (5% H2) atmosphere for 1-2 hours, and the calcined material was etched with 0.01-0.02MNH4HF2 solution at 60-70°C for 10-20 minutes, centrifuged and washed three times with water, and finally freeze-dried to obtain Zn / Cu-BSAN material; (8) 0.1-0.2 g Zn / Cu-BSAN material was suspended in 100-110 mL ethanol, and then 20-30 mL 0.2-0.3 M ethylene disulfide solution was added, stirred at room temperature for 20-25 h, centrifuged and washed with ethanol three times, and dried under vacuum at room temperature to obtain Zn / Cu-BSAN-SHNPs particles; (9) 10-12 mg DOX·HCl and 25-30 mg acetylthioacetate SATA were placed in a 10 mL test tube and dissolved with 3-5 mL DMF, and then 5-10 μL triethylamine was added to the test tube and stirred for 2-3 h to obtain SATA-substituted doxorubicin DOX-SATA solution, which was then diluted with 5-10 mL water, extracted twice with 5-10 mL ethyl acetate, and then washed three times with 1% hydrochloric acid, saturated sodium carbonate and saturated brine in sequence, and then concentrated by rotary evaporation to obtain DOX-SATA particles; (10) 4 mg of the purified DOX-SATA particles obtained in step (9) were dissolved in 2-5 mL of DMF, and the DMF was mixed with 3-4 mg of hydroxylamine hydrochloride (0.5 M) and 2-5 μL of triethylamine. After the chemical reaction was continued in the mixed solution for 1 hour, the product was purified and dried to obtain DOX-SH particles; (11) Dissolve 10-15 mg of DOX-SH particles obtained in step (10) in 10-15 mL of DMSO solution, then add 2-5 mg of Zn / Cu-BSAN-SH obtained in step (8), stir at room temperature for 24 hours and centrifuge at 14000 rpm for 10 min, and finally freeze-dry to obtain Zn / Cu-BSAN-DOX nanoparticles.

3. The method for preparing a double single-atom nanozyme material that can be combined with chemodynamic therapy and sonodynamic therapy according to claim 2, characterized in that: The concentration of Zn(NO3)2 in the methanol solution in step (1) is 18-20 mg·mL -1 The concentration of C4H6N2 in step (2) is 20-25 mg·mL -1 .

4. The method for preparing a double single-atom nanozyme material that can be combined with chemodynamic therapy and sonodynamic therapy according to claim 2, characterized in that: The ZIF-8 nanoparticles described in step (3) are synthesized by reacting 90-97% by weight of methanol, 4-6% by weight of distilled water, 0.01%-0.09% by weight of Zn(NO3)2, and 0.1%-0.3% by weight of C4H6N2.

5. The method for preparing a double single-atom nanozyme material that can be combined with chemodynamic therapy and sonodynamic therapy according to claim 2, characterized in that: The concentration of sodium hydroxide in step (4) is 60-80 mg·mL -1 The mass of cetyltrimethylammonium bromide (CTAB) in step (5) is 1-2 mg·mL -1 The concentration of tetraethyl orthosilicate (TEOS) is 15-20 mg·mL -1 .

6. The method for preparing a double single-atom nanozyme material that can be combined with chemodynamic therapy and sonodynamic therapy according to claim 2, characterized in that: The ZIF-8@SiO2 nanoparticles in step (5) contain 70-85% by weight of ZIF-8 and 15-30% by weight of silicon dioxide.

7. The method for preparing a double single-atom nanozyme material that can be combined with chemodynamic therapy and sonodynamic therapy according to claim 2, characterized in that: The TIPP concentration in the DMF solution in step (6) is 2-5 mg·mL -1 , the concentration of Cu(CH3COO)2·H2O in dimethyl sulfoxide is 2-5 mg·mL -1 .

8. The method for preparing a double single-atom nanozyme material that can be combined with chemodynamic therapy and sonodynamic therapy according to claim 2, characterized in that: The mass ratio of Cu-TIPP to ZIF-8@SiO2 in step (7) is 1:20-1:25, and the concentration of Cu-TIPP in the DMF solution is 2-3 mg·mL -1 The concentration of ZIF-8@mSiO2 in DMF solution is 4-5 mg·mL -1 , the concentration of α,α'-dibromo-p-xylene in DMF solution is 6-9 mg·mL -1 .

9. The method for preparing a double single-atom nanozyme material that can be combined with chemodynamic therapy and sonodynamic therapy according to claim 2, characterized in that: The concentration of Zn / Cu-BSAN in the ethanol solution in step (8) is 1-2 mg·mL -1 The volume ratio of ethanol solution to dithioethylene glycol solution is 3:1-5:1, and the concentration of DOX·HCl in DMF solution is 3-4 mg·mL -1 , the concentration of acetylthioacetate (SATA) in DMF solution is 6-9 mg·mL -1 The concentration of hydroxylamine hydrochloride in DMF solution is 1-2 mg·mL -1 , the volume ratio of triethylamine and DMF is 1:1000-1:2000.